Evaluation of the Functional Performance of the Teachers of Physical Education Using Technique 360° - اسيل حميد عبيد ا.م.د. لمياء عبد الستار (الرياضة المعاصرة)
The objective of this study is to develop the evaluation of the performance of physical education teachers in girls' secondary schools in Baghdad governorate using the multi-lateral evaluation technique (360 ° feedback technology). The problem of the research is to adopt the traditional approach to evaluating the performance of physical education teachers in the general directorates of education In the province of Baghdad, which is based on the opinion of the direct official, which does not achieve the desired results of the adoption of a single source of feedback feedback on the process of evaluating the performance of the function and highlights the importance of research in the need of educational institutions in Iraq to The application of a new management style in the process of evaluating job performance because the rapid development of technology in pushing the world to begin the serious steps to review its various institutions in terms of structure, objectives and functions. The study was based on a questionnaire prepared by the researcher with a five-point scale. Seven forms were distributed at the St. Thomas Secondary School for Girls, with one form for each of the physical education school, one specialist, the secondary supervisor and two female teachers. Analysis of the results Using the mean of arithmetic mean, average mean and variance, this study found a negative gap of (1.182) between the responses of the two parties to the evaluation process, which shows an exaggerated individual in the presence of evaluation criteria, The school of Physical Education at the St. Thomas High School for Girls is exceeding the requirements. The final rate of the assessment was 3,783 out of five. The study ended with the recommendation and directing the attention of the decision makers in the directorates of education towards the adoption of this technique in the evaluation of the job performance. Their reliance on multiple sources in the evaluation process is far from favoritism and bias.